Design of anti-depressant phosphodiester amino acidic Keap1-Nrf2 protein-protein interaction inhibitors - Yi Sun; Jue Wang; Wenxin Ding; Qingqing Qin; Rui Wang; Ruizhi Yu; Jianyu Yan; Ruilin Hou; Guodong Liu; Xiangming Cai; Zhuo Qu; Wannian Zhang; et al. (Redox Biology)
Inhibiting the protein-protein interaction (PPI) between Keap1 and Nrf2 is theoretically an effective and safe strategy for activation of Nrf2 pathway to treat major depressive disorder (MDD). In this study, through bioinformatic analysis of the brain tissues and peripheral blood of MDD patients and depressive mice, we confirmed the involvement of oxidative stress, inflammation, and the Keap1-Nrf2 pathway in depression. Subsequently, we developed a series of phosphodiester amino acidic diaminonaphthalene compounds as Keap1-Nrf2 PPI inhibitors for the first time. Screening using the LPS-stimulated SH-SY5Y and BV2 cell models identified compound 4–95 showing the best anti-oxidative stress and anti-inflammatory efficacy. The ability of 4–95 to penetrate the blood-brain-barrier was significantly enhanced. In a chronic unpredictable mild stress mouse model, treatment with 4–95 effectively ameliorated anxiety and depression behavior and restored serum neurotransmitter levels by promoting the Nrf2 nuclear translocation. Consequently, oxidative stress was reduced, and the expression of synaptic plasticity biomarkers, such as postsynaptic density protein 95 (PSD95) and synapsin 1 (SYN1) were significantly increased, suggesting the recovery of neuronal function. Collectively, our findings demonstrate that the Keap1-Nrf2 PPI inhibitor holds great promise as a preclinical candidate for the treatment of depression.